Hi my name is patty and I am a student taking a pre-calculus course and need help with the following: 5x - 4y = 13 2y + 3x = -1 Would I solve like this, 2y +3x = -1 y = -1/2 -3/2 x solve for x 5x - 4(-1 -3x) = 13 now I need help ? Thank you, Patty. Hi Patty,
What you have is almost correct, there is however an error in the last line. When you substituted y = - ^{1}/_{2} -^{3}/_{2} x) = 13
The next step is to multiply through the expression in parenthes by -4 to get ^{1}/_{2} -^{3}/_{2} x) = 2 + 6 x
^{1}/_{2} -^{3}/_{2} x) = 13
Now use y = - To return to the previous page use your browser's back button. |